Palliative care in undergraduate nursing education: A mixed-methods study - Minosso, Jéssica Sponton Moura; Martins, Maria Manuela Ferreira Pereira da Silva; Oliveira, Maria Amélia de Campos (Journal of Nursing Referência, 2022)
Background: With the progression of the epidemiological transition, palliative care skills should be acquired already in undergraduate nursing education. However, most nursing schools have been slow to adapt to the needs emerging from this new context. Objectives: To identify the perceptions and knowledge of final-year undergraduate nursing students in Brazil and Portugal about palliative care and compare them with their experiences in clinical practice. Methodology: Multicenter, exploratory, and descriptive study with a qualitative approach. Fifteen students were interviewed in 2018: 10 Brazilian students and five Portuguese students. Data were analyzed using Bardin’s content analysis technique. Patricia Benner’s model was used as theoretical framework. Results: The narratives revealed dissatisfaction with the palliative care content in the curricula, frustration with the experiences in clinical practice, and conceptual misconceptions about the theme. Conclusion: The curricula should be adapted and palliative care content integrated into mandatory subjects.